A robust routing protocol for energy and coverage optimization in wireless sensor networks using game theory and heuristic algorithm - Chen, Hao; Wan, Hua-Ping; Ge, Hui-Bin; Luo, Yaozhi (Engineering applications of artificial intelligence, 2026)
Wireless sensor networks (WSNs) are applied to structural health monitoring (SHM) due to their low cost and flexible installation. Reliable WSNs provide effective monitoring data for SHM, which is the foundation for structural condition assessment. However, due to energy consumption and harsh conditions such as high temperatures and corrosion, sensor nodes may run out of energy or malfunction, which can disrupt the network structure and lead to abnormal monitoring data. Cluster routing protocols and fault tolerant methods are extensively employed to reduce node energy consumption and manage sensor faults. In this study, a game theory based fault tolerant routing protocol (FTRP-GT) is proposed to reduce network energy consumption, manage faulty nodes, and extend network lifetime. This protocol offers multiple advantages. First, the optimal number of cluster heads (CHs) was derived, and a game theory based candidate CHs selection method is proposed to consider residual energy, node degree, and node importance. Second, the optimal CHs are obtained from the candidate CHs using the particle swarm optimization (PSO) algorithm. Third, the protocol designs a reusing faulty node (RFN) strategy, which uses the faulty node as a relay node to forward CH data, effectively utilizing the residual energy of faulty nodes and ensuring network stability. The proposed FTRP-GT protocol is evaluated using the monitoring network of Beijing Daxing International Airport. The results show that the FTRP-GT protocol performs better in extending network lifetime and reducing energy consumption compared to other routing protocols.